The influence of different calcium levels, irrigation methods and storage temperatures on the yield, quality and growth potential of G0 mini-tubers - De Villiers, Andre Jaco (Stellenbosch : University of Stellenbosch, 2008)
University of Stellenbosch. Faculty of Agrisciences. Dept. of Agronomy.